Urinary Incontinence and Quality of Life in Female Patients with Obesity - Nygaard, Christiana Campani; Schreiner, Lucas; Morsch, Thiago Picolli; Saadi, Rodrigo Petersen; Figueiredo, Marina Faria; Padoin, Alexandre Vontobel (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Objective To analyze the prevalence of urinary incontinence (UI) in female patients with an indication for bariatric surgery, to investigate the potential risk factors and the impact on quality of life.Methods A cross-sectional study with female patients with obesity. The evaluation consisted of a structured interview, a specific study form and quality of life questionnaires. The Poisson regression was performed to identify independent risk factors related to UI.Results A total of 221 patients were enrolled; 118 of the study participants (53.4%) reported UI episodes. Mixed UI (MUI), stress UI (SUI) only, and urgency UI (UUI) only were reported by 52.5% (62), 33.9% (40) , and 13.5% (16) of these patients respectively. The prevalence of UI was increased by 47% among the women who had given birth vaginally and by 34% of the women who had entered menopause. Vaginal delivery and menopause were identified as independent risk factors related to UI. The mean International Consultation on Incontinence Questionnaire - Short Form (ICIQ-SF) score was 9.36 ± 4.9. The severity of symptoms was considered moderate in 53.3% (63) of the patients with UI.Conclusion Urinary incontinence impacts quality of life negatively, and the prevalence of UI is high among obese patients. In the present study, vaginal delivery and menopause were independently associated with UI.
Keywords: obesity; urinary incontinence; bariatric surgery